Validation and Psychometric Properties of the Arabic Version of the Duke Anticoagulation Satisfaction Scale (DASS) - AlAmmari, Maha; Sultana, Khizra; AlHarbi, Sattam Nawaf; Marenga, Ashwag Saud; AlTuraiki, Abdulrahman; Althemery, Abdullah Uthman; Alfaifi, Abdullah Ali; AlShehri, Asma; Aqeel, Bander Fahad (Frontiers in Pharmacology, 2020)
Background: To assess the health-related quality of life (HRQoL) of oral anticoagulant therapy users, different types of instruments are available, either general or specific tools like Duke Anticoagulation Satisfaction Scale (DASS). These tools allow the clinician to adjust the treatment regimen to focus on increasing anticoagulation adherence and reduce adverse clinical outcomes. This study aims to validate the translated Arabic version of DASS to assess the satisfaction level of patients using oral anticoagulants in the Arab population. Methods: The Duke Anticoagulation satisfaction scale (DASS) was translated into the Arabic language using MAPI group services. DASS was administered to 500 patients receiving anticoagulation with warfarin or apixaban. The generic scale measuring the quality of life EQ5D5L was also administered. Psychometric properties were assessed by Confirmatory Factor Analysis, internal consistency (Cronbach’s Alpha), exploratory factor analysis, convergent and divergent validity, and the correlation between the DASS and demographic variables, clinical characteristics, and the EQ5D5L. Results: 439 subjects answered all the questions. From a total of 25 items, 22 grouped into three factors (limitations, positive impact, and negative impact). Each factor had good internal consistency (Cronbach Alpha 0.78-0.88). All the three factors correlated consistently with EQ5D5L measuring generic quality of life. Conclusion: The psychometric properties of the Arabic DASS version were comparable to the original English version. The Arabic version of the DASS showed very good reliability and validity. It can be used by health care professionals in other settings of anticoagulation clinics to assess patients ‘satisfaction and limitations to anticoagulant treatment.